Sectorial growth, Exchange rate and Fiscal policy in Developing Economies: The Interlinkages - Fazal, Snober; Bhatti, Muhammad Azhar; Ahmad, Tusawar Iftikhar (iRASD Journal of Economics, 2019)
The study examined the interdependence of sectorial growth, exchange rate and fiscal policy by simultaneous equation model for 50 developing economies over the time period of 2000 to 2014. Industrial GDP, service sector GDP, exchange rate, tax revenue are endogenous variables, while capital formation, foreign direct investment, trade, inflation, foreign aid, external debt and money supply are instruments. The study has 4 system of equations and estimated by simultaneous equations models (SEMs) through three-stage least squares (3SLS) estimator presented by (Zellner & Theil, 1962), the result of the study indicates that sectorial growth and fiscal policy have positive relation because tax exemption or reduction generate great impact on sectoral growth. Sectorial growth and exchange rate have a positive relation. The study also indicates that the exchange rate and fiscal policy are negatively related. An increase in government expenditure (spending) shows a decrease in the exchange rate. So the government of developing economies should increase revenues from non-tax sources instead of taxes, an increase in taxes decrease the exchange rate and ultimately increased in the sectoral growth.